Using Language Learning Strategies to Enhance Writing Skills: An Empirical Study of Student-Centered Learning Approaches In Saudi Context - Nukapangu, Venkanna; Kumar, Tribhuwan (Ijaz Arabi Journal of Arabic Learning, 2024)
Arabic is the mother tongue of Saudi students. The current research project aims to investigate the extent to which the learning strategies utilized by PSAU students effectively enhance their writing skills and modify their attitudes toward writing. In the present study, the methodology used has been qualitative and quantitative, which is a mixed approach. The reason behind using a mixed approach is that this study aimed to collect qualitative and quantitative data concerning the learners’ writing strategies during writing classes. The research uses observation, questionnaires, and interviews to collect the data. For the study, around 250 students will be selected from the writing courses of various PSAU colleges. The effectiveness of the students’ strategies used in learning employed by the students of PSAU for promoting writing skills and changing passive attitudes towards writing is expected to reveal the role and usefulness of improving writing skills as a result of using students’ strategies.